Konsep Pedagogi Emansipatif Menurut Jacques Ranciere - Ayi Hambali; Rakhmat Hidayat (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2020)
The purpose of this article to analyze the thought of Jacques Ranciere in the practice of emancipatory education. Ranciere is one of the new generation of French philosopher.This article written by library research method whichis relevant with Ranciere. He revealed a critique of the explicative order he calls the myth of pedagogy which dominate educational practices today. Furthermore, the result of this study shows that the conception of education in Ranciere thought seeks to show ways to envision pedagogical practice as a form of intellectual emancipation, or in other words, a practice which verifies the equality of human intelligence. Realized in practice through teaching methods introduced by Josep Jacotot with the name of Universal Teaching. To confirm the true nature of humanity that: "all men are equally intelligence".